1980
DOI: 10.1029/ja085ia02p00753
|View full text |Cite
|
Sign up to set email alerts
|

Microscale instabilities in stream interaction regions

Abstract: A theoretical investigation of the microstructure of solar wind stream interaction regions is presented. We discuss the role of several electrostatic kinetic instabilities which may be important within the stream interface and the compression region. Inside of 1 AU the interface is likely to be stable against the electrostatic streaming instabilities considered. Between 1 and 2 AU we argue that the interface will excite the magnetized ion‐ion instability. The compression region is also found to be unstable bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…is similar to what has been observed by Helios at 0.3-1 AU from the Sun [Beinroth and Neubauer, 1981]. Eviatar and Goldstein [1980] discussed theoretically several plasma instabilities which were associated with stream interfaces and the compression region. They found that beyond I AU, the possible range of frequencies excited in these regions extends from the lower hybrid (due to the modified twostream instability) through the ion acoustic frequency range to harmonics of the electron cyclotron frequency.…”
Section: Summary Of the Observationssupporting
confidence: 85%
“…is similar to what has been observed by Helios at 0.3-1 AU from the Sun [Beinroth and Neubauer, 1981]. Eviatar and Goldstein [1980] discussed theoretically several plasma instabilities which were associated with stream interfaces and the compression region. They found that beyond I AU, the possible range of frequencies excited in these regions extends from the lower hybrid (due to the modified twostream instability) through the ion acoustic frequency range to harmonics of the electron cyclotron frequency.…”
Section: Summary Of the Observationssupporting
confidence: 85%
“…This instability had been studied earlier in the electrostatic limit by Stepanov [1973] reported detailed studies of growth rate variations with 0; they showed that at v o • v e, the maximum growth rate typically occurs at Electromagnetic or nonzero fi effects on the modified two-_ stream instability were first examined in detail by Lemons and Gary [1977], who showed that as fie is increased, Ym decreases but also shifts to larger values of k:/k. This subject was pursued in greater detail by Eviatar and Goldstein [1980] and Wu et al [1983]. In particular, the latter demonstrated that the modified two-stream instability (or, in their terminology, the "kinetic cross-field streaming instability") is not stabilized by electromagnetic effects' since the •e stabilization criterion of McBride and Ott [1972] requires nonresonant electrons and 0 very close to re/2, it may apply to the ion/ion lower hybrid instability but not to the modified two-stream instability.…”
supporting
confidence: 68%
“…However, it may be possible to use existing particle data to indirectly infer the relative {mportance of the two electron/ion instabilities in the following A recent experimental study [Bavassano-Cattaneo et al, 1986] has demonstrated the existence of a magnetic foot at some interplanetary shocks. We expect that these structures are also due to the presence of ions reflected from the shock and that our theory (as well as the earlier work of Papadopoulos [1973] and Eviatar and Goldstein [1980]) should apply to the generation of lower hybrid frequency noise at interplanetary shocks as well.…”
Section: In This Papermentioning
confidence: 75%
See 1 more Smart Citation